2018
DOI: 10.3389/fpls.2018.00089
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Transcripts Mapping Coupled with Expression Quantitative Trait Loci Mapping Reveal the Molecular Network Regulating the Apetalous Characteristic in Brassica napus L.

Abstract: The apetalous trait of rapeseed (Brassica napus, AACC, 2n = 38) is important for breeding an ideal high-yield rapeseed with superior klendusity to Sclerotinia sclerotiorum. Currently, the molecular mechanism underlying the apetalous trait of rapeseed is unclear. In this study, 14 petal regulators genes were chosen as target genes (TGs), and the expression patterns of the 14 TGs in the AH population, containing 189 recombinant inbred lines derived from a cross between apetalous “APL01” and normal “Holly,” were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The genotypes of this population and two parents were analyzed using simple sequence repeat (SSR) markers and the Illumina (San Diego, CA, USA) Brassica 60 K Infinium array by DNA Landmarks (Saint-Jean-sur-Richelieu, QC, Canada) in a previous study [ 75 ]. A high-density single nucleotide polymorphism (SNP) linkage map incorporating 2755 bins (involving 11,458 SNPs) and 57 SSRs, covering 2027.53 cM with an average marker interval of 0.72 cM was developed for QTL mapping of the apetalous trait [ 75 , 76 ], seed fatty acid composition [ 77 ], flowering time [ 78 ], and stem mechanical strength [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…The genotypes of this population and two parents were analyzed using simple sequence repeat (SSR) markers and the Illumina (San Diego, CA, USA) Brassica 60 K Infinium array by DNA Landmarks (Saint-Jean-sur-Richelieu, QC, Canada) in a previous study [ 75 ]. A high-density single nucleotide polymorphism (SNP) linkage map incorporating 2755 bins (involving 11,458 SNPs) and 57 SSRs, covering 2027.53 cM with an average marker interval of 0.72 cM was developed for QTL mapping of the apetalous trait [ 75 , 76 ], seed fatty acid composition [ 77 ], flowering time [ 78 ], and stem mechanical strength [ 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most previous GWAS studies in rapeseed focused on a limited number of phenotypic traits and/or only a single omics level. Some recent studies integrated at least two omics levels, such as Li et al (2023) who studied the seed oil content in rapeseed using a marker metabolite-based multi-omics analysis, Li, Yao, et al (2018) who integrated QTL and eQTL mapping to study fatty acid content, flowering time and growth-related traits, Yu et al (2018) who coupled QTL and eQTL mapping focusing on the apetalous characteristic or Zhang et al (2022) who dissected the genetic architecture of seed coat content in B. napus using a multi-omics analysis. Schaefer et al (2018) demonstrated in maize that integrating co-expression networks with GWAS can be a powerful approach to prioritise candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) who integrated QTL and eQTL mapping to study fatty acid content, flowering time and growth‐related traits, Yu et al. (2018) who coupled QTL and eQTL mapping focusing on the apetalous characteristic or Zhang et al. (2022) who dissected the genetic architecture of seed coat content in B. napus using a multi‐omics analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, apetalous rapeseed decreased the infections (D. I. Jamaux, and Spire, D., 1999; K. Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%